When Dragon Met Jasmine: Domesticating English Names in Chinese Social Interaction - Henry, Eric S. (Anthropologica, 2022)
The acquisition and use of English names in China is usually treated by scholars as evidence of growing Westerniza tion by Chinese speakers, who are forced to acquire these names to successfully converse with foreigners. In this article, I draw on an ethnographic examination of Chinese English names and naming narratives to reveal the indexical connections between names and meanings. Rather than acting as simple indices of Western identities, English names are dynamic signifiers in a complex social field of interactions that are distinctly Chinese. The characteristics of desirable English names borrow from a cultural pragmatics of Chinese naming instead of foreign norms.